PENGEMBANGAN FLIPBOOK DIGITAL “SAHABAT PANCASILA” BERBASIS VALUE-REFLECTIVE PEDAGOGY (VRP) UNTUK SISWA KELAS IV SDN KEMAYORAN 2 - Rifka Aidah Fatin; Devita Rizkia Ramadhani S; Mutiara Khoirus Tsani; Mujtahidin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The rapid degradation of affective character and empathy among elementary school students in the digital era poses a critical challenge to civic education. This study addresses this issue by developing a valid, practical, and effective digital flipbook learning media named